Assessing the Relation Between Covid-19 Perception and Acceptance of the Covid-19 Vaccine in Kenya. - Kivuva, Eva, Wavinya (My University, 2021)
PURPOSE: Since the start of the Covid-19 pandemic in 2019 in China and its spread, it continues to terrorize the Kenyan population with new infections and death cases daily. This study was done to determine if the perception of the disease influenced vaccine acceptance within the Kenyan population. METHODS: Electronically shared questionnaires were used to conduct this survey in the Kenyan adult population in January and February 2021 due to Covid-19 restrictions, to evaluate the Kenyan populations’ Covid-19 perception and relation to Covid-19 vaccine acceptance rate. One-way ANOVA was performed to check whether the perception of respondents and acceptance of the vaccine differed significantly and correlation was done to evaluate the relationship between the perception and vaccine acceptance. RESULTS: Out of total sum of 659 participants, 451(68%) perceived the existence of Covid-19 in the country; 338 (75%) were willing to take the vaccine if it was made available to them. Noticeable differences between the perception and acceptance rate of the vaccine across different demographic characteristics. CONCLUSION: Covid-19 perception strongly relates to the acceptance of the vaccine in the Kenyan population.